SOCIAL SUPPORT RECEIVED BY SUBSTANCE ABUSER IN SLEMAN REGENCY - Rizqi Wahyu Hidayati; Indah Winarni; Septi Dewi Rachmawati (Journal of Nursing Science Update (JNSU), 2020)
Substance abuse is a global problem, including in Indonesia, especially Yogyakarta. Thisprovince has the highest prevalence of substance abuse among students in Indonesia.Substance abuse has negative impacts on health, both physically and psychologically.Because of that, recovery is needed to restore the function and role of the individual.When they undergo the recovery process, social support is required. This study aimedto determine the meaning of experience in undergoing the process of recovery ofsubstance dependence during receiving social support. This study used qualitativewith interpretative phenomenology design. Participants were taken using purposivesampling method, there were 9 participants included in this study. The data retrievaltechnique through in-depth interviews with an open-ended question. The data analysisused was Interpretative Phenomenological Analysis (IPA) method. Based on the results,themes were obtained: (1) Understanding recovery is a long life process; (2) Receivinga whip which saves you from the downturn; (3) Not being a part of the world of life; (4)Gain a sense of humanity in society; (5) Gain the whole support to rise from adversity.The result showed that the support was interpreted as a lash, meaning that it could giveuncomfortable feelings, such as forced to change, received too much advice, or negativecomments. However, it also could increase the motivation to move forward for the clients.Finally, researchers suggest further research to explore the relation of social support andgender issues when they underwent substance recovery.